2018
DOI: 10.1111/eos.12590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycerol on reconstructed human oral mucosa

Abstract: The majority of severely ill patients experience dry mouth. For institutionalized patients, this condition is commonly treated using glycerol as a lubricant. However, because of its possibly desiccating effect, some countries do not advocate the use of glycerol. This study aimed to investigate dose‐dependent effects of glycerol on homeostasis and tissue integrity of in vitro‐reconstructed normal human buccal mucosa (RNHBM). Primary keratinocytes and fibroblasts were isolated and expanded from biopsies of mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Glycerol acts as a solvent and increases the solubility of some components in water, therefore it can be a substitute (to some extent) of ethyl alcohol and can also be used in formulation with ethyl alcohol and water together [ 137 , 138 ]. It is commonly used as a lubricant and emollient, as it provides smoothness, but due to its hygroscopic properties which may cause desiccation [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycerol acts as a solvent and increases the solubility of some components in water, therefore it can be a substitute (to some extent) of ethyl alcohol and can also be used in formulation with ethyl alcohol and water together [ 137 , 138 ]. It is commonly used as a lubricant and emollient, as it provides smoothness, but due to its hygroscopic properties which may cause desiccation [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study revealed that glycerol affects the mucosa homeostasis (increasing epithelial thickness, proliferation and apoptosis) if glycerol concentration is above 42.5% and does not affect mucosal integrity. Affected homeostasis and increased proliferation may result in DNA damage accumulation and pose potential risks in long-term exposure [ 139 ]. Glycerine is also an ingredient in the liquid used in electronic cigarettes, with no toxicologically relevant effects [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…É frequentemente utilizado na produção de produtos com função hidratante por possuir uma alta capacidade de atrair moléculas de água. Apresenta 1283 entradas em produtos de prateleira no DrugBank database (DB09462), e é frequentemente utilizado em associação com outras moléculas como a carboximetilcelulose (CMC) na produção de colutórios e saliva artificial no controle da xerostomia, e também na produção de colírios para o controle da xeroftalmia (Furness et al, 2011;Kvalheim et al, 2019).…”
Section: Integração Dos Dados De Metabolômica E Proteomicaunclassified